Examining the Impact of Work Engagement and Job Satisfaction on Employee Performance Through Organizational Commitment in Regional Government - Prajadiredja, Muhammad Daffa Rizq; -, Zunaidah -; Cahyadi, Afriyadi (At-Tadbir : jurnal ilmiah manajemen, 2026)
This study investigates the effects of work engagement and job satisfaction on employee performance, highlighting the mediating role of organizational commitment within the framework of the Job Demands–Resources (JD-R) theory. Conducted in the public sector of South Sumatra Province, data was collected from civil servants using a quantitative survey approach and analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). Work engagement and job satisfaction were measured with established multidimensional scales, while organizational commitment and employee performance were assessed using validated constructs. The findings demonstrate that both work engagement and job satisfaction positively and significantly impact employee performance, both directly and indirectly through organizational commitment. Organizational commitment acts as a crucial bridge that transforms motivation and satisfaction into increased task achievement, loyalty, creativity, and responsibility. This integrative model confirms the relevance of psychological resources in sustaining high performance even within bureaucratic environments. The study contributes theoretically by reinforcing the JD-R model’s applicability to public sector contexts, and offers practical insights for human resource management aimed at fostering engagement, satisfaction, and commitment. Recommendations for future research include expanding sample scope and employing longitudinal approaches to capture dynamic changes in employee attitudes and outcomes within government organizations.